Synthesis, Spectral Characterization and Biological Activity of 2- [2‾ - (1-Amino -1, 5- Dinitrophenyl) azo]-Imidazole - Abd Al-Sadda HK (Journal of Global Pharma Technology, 2016)
The preparation and spectral identification of ligand 2-[1‾-(1-Amino- 1,5-Dinitrophenyl) azo]-Imidazole (ADNPAI) were prepared by reacting a dizonium chloride salt solution of 2,4-Dinitrophenylhydrazine with imidazole in alkaline ethanol solution. Azo dye ligand Prepared have been characterized by analytical data, Infrared, Electronic spectral data, XRD, SEM, Thermal analysis (TG-DSC-DTG), UV-Vis, and magnetic susceptibility. The biological activity azo dye ligand were tested invitro against the sensitive organisms Staphylococcus aureus (Gram-positive) and Escherichia coli, Pseudomonas aeruginosa (Gram-negative) by agar plate different technique. The activity data show appearance the ligand azo dyes prepared apparent highly active against to all the bacteria species tested.Keywords: Azo imidazole, ADNPAI, Thermal analysis, SEM, Antibacterial.